Cognitive impairment in patients with severe psoriasis - Marek-Józefowicz, Luiza; Jaracz, Marcin; Placek, Waldemar; Czajkowski, Rafał; Borkowska, Alina (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Psoriasis is a chronic inflammatory skin disease, in which an important role is played by psychological factors. Aim : To evaluate the frontal cognitive functions in patients with psoriasis. Material and methods : The study included 188 subjects (97 patients with psoriasis and 91 healthy controls). To assess the dorsolateral prefrontal cortex functions, the Trail Making Test and the Stroop test were applied. Severity of psoriasis was assessed by means of the PASI index. Results : Compared to healthy subjects, psoriatics scored lower in neuropsychological tests assessing memory and executive functions. Conclusions : Cognitive dysfunction disclosed by neuropsychological assessment of frontal functions was evident in patients with psoriasis.